Performance comparison of conventional and strained FinFET inverters. (September 2016) - Dubey, Shashank; Kondekar, Pravin N.
Abstract: In this paper, we have investigated the effect of tensile and compressive stress on the performance matrices of complementary FinFET inverters. The static and dynamic characteristics have been compared with conventional Silicon FinFET inverter. Epitaxially grown Silicon–Germanium (SiGe) and Silicon–Carbide (SiC) source/drain (S/D) are used as stressors for p- and n-FinFET, respectively, over Bulk and SOI substrates. Further, the effect of asymmetric doping at source/drain have been analyzed and compared with the symmetric one. It has been found from the transient response that due to strain, the mobility is enhanced across channel and the switching speed has increased. However, for unequal doping, due to unbalanced stress the propagation delay has been enhanced upto 20% in comparison to symmetric inverters. The minimum propagation delay of 45 ns for strained Bulk inverter has been found due to high driving current in FinFETs. The fin shape dependence changes also has been investigated by varying top fin width. Rectangular to triangular fin shapes variation caused reduction in delay of about 10–13%.